The Role of Pr55(gag) in the Annealing of tRNA(3)(Lys) to Human Immunodeficiency Virus Type 1 Genomic RNA - Cen, Shan (American Society for Microbiology, 1999)
During human immunodeficiency virus type 1 (HIV-1) assembly, the primer tRNA for the reverse transcriptase-catalyzed synthesis of minus-strand strong-stop cDNA, tRNA(3)(Lys), is selectively packaged into the virus and annealed onto the primer binding site on the RNA genome. Annealing of tRNA(3)(Lys) in HIV-1 is independent of polyprotein processing and is facilitated in vitro by p7 nucleocapsid (NCp7). We have previously shown that mutations in clusters of basic amino acids flanking the first Cys-His box in NC sequence inhibit annealing of tRNA(3)(Lys) in vivo by 70 to 80%. In this report, we have investigated whether these NC mutations act through Pr55(gag) or Pr160(gag-pol). In vivo placement of tRNA(3)(Lys) is measured with total viral RNA as the source of primer tRNA-template in an in vitro reverse transcription assay. Cotransfection of COS cells with a plasmid coding for either mutant Pr55(gag) or mutant Pr160(gag-pol), and with a plasmid containing HIV-1 proviral DNA, shows that only the NC mutations in Pr55(gag) inhibit tRNA(3)(Lys) placement. The NC mutations in Pr55(gag) reduce viral infectivity by 95% and are trans-dominant-negative, i.e., they inhibit genomic placement of tRNA(3)(Lys) even in the presence of wild-type Pr55(gag). This dominant phenotype may indicate that the mutant Pr55(gag) is disrupting an ordered Pr55(gag) structure responsible for the annealing of tRNA(3)(Lys) to genomic RNA.